Antioxidant and α-Amylase Inhibitory Property of Phyllanthus virgatus L.: An In Vitro and Molecular Interaction Study. (19th June 2013) - Hashim, Arshya; Khan, M. Salman; Khan, Mohd. Sajid; Baig, Mohd. Hassan; Ahmad, Saheem
Abstract : The present study on Phyllanthus virgatus, known traditionally for its remedial potential, for the first time provides descriptions of the antioxidant and inhibition of α -amylase enzyme activity first by in vitro analyses, followed by a confirmatory in silico study to create a stronger biochemical rationale. Our results illustrated that P. virgatus methanol extract exhibited strong antioxidant and oxidative DNA damage protective activity than other extracts, which was well correlated with its total phenolic content. In addition, P. virgatus methanol extract strongly inhibited the α -amylase activity (IC50 33.20 ± 0.556  μ g/mL), in a noncompetitive manner, than acarbose (IC50 76.88 ± 0.277  μ g/mL), which showed competitive inhibition. Moreover, this extract stimulated the glucose uptake activity in 3T3-L1 cells and also showed a good correlation between antioxidant and α -amylase activities. The molecular docking studies of the major bioactive compounds (9, 12-octadecadienoic acid, asarone, 11-octadecenoic acid, and acrylic acid) revealed via GC-MS analysis from this extract mechanistically suggested that the inhibitory property may be due to the synergistic effect of these bioactive compounds. These results provide substantial basis for the future use of P. virgatus methanol extract and its bioactive compound in in vivo system for the treatment and management of diabetes as well as in the related condition of oxidative stress.